The Pronunciation of English Fricatives by Nigerian Undergraduates: A Study of Situation in Akwa Ibom State University (Eurasian Journal of Media and Communications, 2023)
This research set out to examine the pronunciation of English fricatives by Nigerian undergraduates. The theoretical bases were systemic functional grammar and descriptive linguistics. Ten undergraduate students from eight Departments of Akwa Ibom State university were randomly selected to read a passage and eleven sentences containing the nine fricative consonants of English. Their performances were recorded with android phone and played back several times for study analysis. It was discovered that voiceless fricatives posed no problem of articulation to the informants irrespective of position of occurrence. On the contrary, the voiced fricatives could not be articulated appropriately especially at word-final positions. The voiced palato-alveolar fricative is the strangest sound and could not be realized by any informant in all positions. It is concluded that mispronunciation of English phonemes can impede understanding and by extension, communication. I suggest that lecturers of English in L2 situations should emphasize regular practice on English fricatives by students.